1988
DOI: 10.1128/jb.170.10.4652-4657.1988
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of tetrapyrrole synthesis by light in chemostat cultures of Rhodobacter sphaeroides

Abstract: Control of bacteriochlorophyll (Bchl), magnesium protoporp}yrin monomethyl ester (MgPME), cytochromes, and coproporphyrin by light was studied with chemostat cultures of Rhodobacter sphaeroides growing at a constant dilution rate. By increasing the growth-limiting light energy flux from 10 to 55 W/m2, specific Bchl contents decreased from 19.3 to 7.9 nmol/mg of protein. This was strictly proportional to a decrease in the ratio of B800-850 to B875 light-harvesting complexes. MgPME levels increased from 1.5 to 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
(29 reference statements)
1
7
0
Order By: Relevance
“…Furthermore, chlorophyll a and chlorophyll b increase the stability of the nuclear-encoded LHCI and LHCII chlorophyll a/b apoproteins (31,32). Likewise, bacteriochlorophyll-binding proteins of photosynthetic bacteria turn over rapidly when bacteriochlorophyll levels are limiting (33)(34)(35). In higher plant chloroplasts, the regulatory mechanism described here affects the accumulation of a large number of abundant chloroplast proteins, giving it special significance during chloroplast biogenesis.…”
Section: Resultsmentioning
confidence: 90%
“…Furthermore, chlorophyll a and chlorophyll b increase the stability of the nuclear-encoded LHCI and LHCII chlorophyll a/b apoproteins (31,32). Likewise, bacteriochlorophyll-binding proteins of photosynthetic bacteria turn over rapidly when bacteriochlorophyll levels are limiting (33)(34)(35). In higher plant chloroplasts, the regulatory mechanism described here affects the accumulation of a large number of abundant chloroplast proteins, giving it special significance during chloroplast biogenesis.…”
Section: Resultsmentioning
confidence: 90%
“…Most of the attention has been devoted to regulation by oxygen tension (6,8,15,39), light intensity (1,5,23), DNA supercoiling (40), and the effects of the recently discovered pufQ gene (3,16). Relatively little attention has been paid to the interrelationships between heme and bacteriochlorophyll syntheses.…”
Section: Discussionmentioning
confidence: 99%
“…The biosynthesis of Bchl in both R. capsulatus and R. sphaeroides is known to be inhibited by high light intensities and by high oxygen tension (6,13,28,29). Yet, it has been shown that high oxygen tension does not repress transcription of bch genes to the same extent as oxygen represses transcription of thepuc,puh, andpufoperons (7,12,21,43).…”
mentioning
confidence: 99%